Introduction to Plasma Physics - Goldston, R.J; Rutherford, P.H (New York : Taylor & Francis, 1995)
Introduction to Plasma Physics is the standard text for an introductory lecture course on plasma physics. The text$1 (Bs six sections lead readers systematically and comprehensively through the fundamentals of modern plasma physics. Sections on single-particle motion, plasmas as fluids, and collisional processes in plasmas lay the groundwork for a thorough understanding of the subject. The authors take care to place the material in its historical context for a rich understanding of the ideas presented. They also emphasize the importance of medical imaging in radiotherapy, providing a logical link to more advanced works in the area. The text includes problems, tables, and illustrations as well as a thorough index and a complete list of references.s
Includes Appendix 477-486p.; Index 487-491p.
Keywords: Plasma physics; Physics